Epidemiology of domestically acquired hepatitis E virus infection in Japan: assessment of the nationally reported surveillance data, 2007–2013 - Kanayama, Atsuhiro; Arima, Yuzo; Yamagishi, Takuya; Kinoshita, Hitomi; Sunagawa, Tomimasa; Yahata, Yuichiro; Matsui, Tamano; Ishii, Koji; Wakita, Takaji; Oishi, Kazunori (Journal of medical microbiology, 2015)
In recent years, there has been an increase in the number of reported hepatitis E virus (HEV) infections from developed countries. To describe recent trends in notification and potential risk groups and risk factors in Japan, HEV infection cases and demographic, food consumption, clinical and laboratory data reported during 2007-2013 were analysed. In total, 530 HEV infections were reported during 2007-2013. Amongst 462 domestic cases, the mean age was 56.5 years (sd 13.9) and 80.1 % were male. Forty-three cases (9.3 %) were asymptomatic, amongst which 11 were detected from blood donations. Whilst ∼50 cases were reported annually during 2007-2011, the number of reported cases increased to 121 in 2012 and 126 in 2013. The increase was characterized by a rise in the number of domestic, symptomatic cases (P = 0.05) and cases confirmed by anti-HEV IgA detection (P < 0.01). HEV genotypes G3 and G4 were consistently dominant. The major suspected source of infection was food-borne, and the major suspected foods were pig, wild boar and deer meat. The observed increase during 2012-2013 was most likely due to the coverage of the anti-HEV IgA assay by the National Health Insurance system in Japan in October 2011 and its acceptance for surveillance purposes. However, the increase was not associated with detection of asymptomatic cases. Moreover, males aged 50-69 years remained as the high-risk group, and pork and other meats continued to be the most suspected items. Our findings indicated that HEV infection is an emerging and important public health concern in Japan.